A Video Assisted Teaching on Preventing Method of School Bullying among Secondary School Teachers in Selected Urban Area of Vadodara (International Journal of Nursing Education, 2019)
Background: This study was designed to investigate the factors affecting prevention of school bullying among school teachers. The validity and reliability of research instruments was established and data was collected from 60 teachers selected from urban school of vadodara using the purposive sampling method. This formed the basis of the detailed analysis and conclusions and recommendations. Aims and objectives: The aim of this study is to find out the factors contributing prevention of school bullying among school teachers. Material and method: Pre-experimental research design was adopted to achieve the goal of the study. The tool consists of one parts First part consists socio demographic data consists of Self structured questionare. 60 samples were collected from selected school of Vadodara by purposive sampling technique. Result: This study was undertaken to assess the effectiveness of teaching programme, regarding prevention on school bullying among school teachers. The study involves one group pre- test post-test pre experimental design with purposive sampling technique, 60 samples of school teachers was selected on the basis of inclusion and exclusion criteria. A conceptual framework used for this study was modified “king?s goal attainment model.” Analysis of obtained data was planned based on the objectives and hypothesis of the study, both descriptive and inferential statistics were used for the analysis of the data. The data was interpreted in the forms of tables and graphs. The calculated “t” value 23.31was greater than the tabulated “t” value at 0.05 levels. Data shows there was significant difference between pre test and post test level of knowledge score. Hypothesis H1 accepted Conclusion: The following conclusion can be drawn from the study findings, which are supported by evidence from the other literature;the self-administered questionare has shown remarkable difference between pre-test and post-test. & vedio assisted programme was effective among teachers